(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Solidarity is information and variety is obliviousness. Universal fraternity of man is the vitalcomponent of his patriotism. He put stock in uniformity and common participation among the countries.Universal fraternity can lay down a good foundation for itself just through strict amicability and socialtrade. He says that the rich countries should help helpless countries. Then, at that point, the global welldisposed connection would be a reality since step by step unique strict faction are making struggle andannihilating the sensation of fraternity. Vivekananda trusted in the uniformity among all countries. He wentagainst the British rule in India. Since all countries are equivalent, no one is better than another. Nocountry has right to lead others. He never preferred conflict and triumph. Vivekananda lectured stricthumanism as the premise of world solidarity. He said each individual is a piece of God. God is to beperceived by everybody. It is a not unexpected conviction that the assistance to humanity isadministration to God. Everyone should help other individuals. Vivekananda’s humanism depended onhis mysticism. Spuitualism gave a personality to man and set up the uniformity of man. For him personis the best creation in the whole world. Human existence is generally valuable and significant. Man isbetter than any remaining being on the planet. Vivekananda says that religion is a science and each workought to be made by the person to set up reality. Each individual has right to apply his motivation toknow reality. He said the idea of adhikarvad, distance, concealment of ladies’ right are all against theorders of a cultivated society or country or the lessons of religions. Azad appended extraordinarysignificance to collective congruity and to him Hindu-Muslim solidarity was fundamental for bringingopportunity. While tending to a commonplace gathering of the Khilafat Movement at Agra on 25October, 1921, he alluded to Hindu-Muslim participation as the pledge of the Prophet Mohammad,entered between the Muslims and different occupants of Medmah to build up a functioning partnershipfor normal defence.Azad utilized the key expression ’Ummat-I-Wahidd’ (single country) for a ’jointHindu-Muslim Nation’. Maulana Azad was basically a strict man yet he was objective, liberal and modemin his thinkmg and logical and authentic in his viewpoint.